2017
DOI: 10.1038/s41598-017-18155-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological stabilization and KPZ scaling by electrochemically induced co-deposition of nanostructured NiW alloy films

Abstract: We have assessed the stabilizing role that induced co-deposition has in the growth of nanostructured NiW alloy films by electrodeposition on polished steel substrates, under pulsed galvanostatic conditions. We have compared the kinetic roughening properties of NiW films with those of Ni films deposited under the same conditions, as assessed by Atomic Force Microscopy. The surface morphologies of both systems are super-rough at short times, but differ at long times: while a cauliflower-like structure dominates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…A more detailed description of a given surface thus needs to consider also other, higher-order moments or even the full power spectrum [ 33 ]. Indeed, a few recent studies have shown that the physical behavior of rough surfaces, for instance during thin film deposition, depends non-trivially on higher-order moments of the surface height distribution such as surface skewness ( Ssk ) and kurtosis ( Sku ), which thus need to be carefully characterized in detail [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed description of a given surface thus needs to consider also other, higher-order moments or even the full power spectrum [ 33 ]. Indeed, a few recent studies have shown that the physical behavior of rough surfaces, for instance during thin film deposition, depends non-trivially on higher-order moments of the surface height distribution such as surface skewness ( Ssk ) and kurtosis ( Sku ), which thus need to be carefully characterized in detail [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the existence of an independent local roughness exponent α loc that characterizes the local interface fluctuations and differs from the global roughness exponent α obtained by, for instance, the global width. This phenomenon is referred to as anomalous roughening and has received much attention in the last few years because its commonness in experiments [9][10][11][12][13][14][15][16][17][18][19][20][21]. Current theoretical knowledge has firmly established [22] that, indeed, the existence of power-law scaling of the correlation functions (i.e., scale invariance) does not determine a unique dynamic scaling form of the correlation functions.…”
Section: Introductionmentioning
confidence: 99%
“…. , we compare this value with experiments in electrochemically induced co-deposition of nanostructured NiW alloy films, z 1.6 (2) [70], dynamics in chemical vapor deposition in silica films, z 1.6 (1) [71], on semiconductor polymer deposition z 1.61 (5) [6], and in excess of mutational jackpot events in expanding populations revealed by spatial Luria-Delbrück experiments, z 1.61 [72]. Thus, we have an agreement with different kinds of recent experiments, and very precise simulations [53], it is unlikely to be just a numerical coincidence.…”
Section: The Hidden Symmetrymentioning
confidence: 97%